Analysis on Encryption and Compression Techniques for Information Security - Mamidisetti, Gowtham; Makala, Ramesh; Teja, Ravi K (International Journal of Computer Sciences and Engineering, 2025)
This paper has investigated some of the encryption and compression techniques. The paper has also examined the implication of these techniques for the future of information security. Indeed, the threat environment has combined with corporate networks and made data security more complex. Therefore, an increasing number of data network users, who have turned to the cloud, have strived to secure their information systems beyond conventional virus scanners and firewalls. With an increasing demand for responsive information security systems, various techniques of data encryption and compression have evolved. Some of the devices, platforms, or information systems that have been targeted by these trends include websites, personal databases, and computers. Some of the specific algorithms that have been employed in data encryption include RiverShamir-Adleman (RSA) algorithm (in asymmetric encryption) and include Rivest Cipher (RC6) and Data Encryption Algorithm (DES) (in symmetric encryption). On the other hand, selected algorithms that have been used towards successful lossless data compression include lossless predictive coding, Arithmetic coding, Lempel-Ziv-Welch (LZW) compression, Huffman coding, and Run Length Encoding. These algorithms have gained application to situations involving platforms such as word processing files, tabular numbers, and executable codes. For lossy data compression, some of the algorithms that have gained increasing application include lossy predictive coding, wavelet coding, and transform coding. The implication for the future is that data encryption and compression techniques that will be responsive to the dynamic nature of the threat environment might prove successful in achieving the intended goals of data encryption and compression processes, hence assuring information system security.